Bacteriophages Are Good Estimators of Human Viruses Present in Water - Ballesté, Elisenda; Blanch, Anicet R.; Mendez, Javier; Sala-Comorera, Laura; Maunula, Leena; Monteiro, Silvia; Farnleitner, Andreas H.; Tiehm, Andreas; Jofre, Joan; García-Aljaro, Cristina (Frontiers in Microbiology, 2021)
The detection of fecal viral pathogens in water is hampered by their great variety and complex analysis. As traditional bacterial indicators are poor viral indicators, there is a need for alternative methods, such as the use of somatic coliphages, which have been included in water safety regulations in recent years. Some researchers have also recommended the use of reference viral pathogens such as noroviruses or other enteric viruses to improve the prediction of fecal viral pollution of human origin. In this work, phages previously tested in microbial source tracking studies were compared with norovirus and adenovirus for their suitability as indicators of human fecal viruses. The phages, namely those infecting human-associated Bacteroides thethaiotaomicron strain GA17 (GA17PH) and porcine-associated Bacteroides strain PG76 (PGPH), and the human-associated crAssphage marker (crAssPH), were evaluated in sewage samples and fecal mixtures obtained from different animals in five European countries, along with norovirus GI+GII (NoV) and human adenovirus (HAdV). GA17PH had an overall sensitivity of ≥83% and the highest specificity (>88%) for human pollution source detection. crAssPH showed the highest sensitivity (100%) and specificity (100%) in northern European countries but a much lower specificity in Spain and Portugal (10% and 30%, respectively), being detected in animal wastewater samples with a high concentration of fecal indicators. The correlations between GA17PH, crAssPH, or the sum of both (BACPH) and HAdV or NoV were higher than between the two human viruses, indicating that bacteriophages are feasible indicators of human viral pathogens of fecal origin and constitute a promising, easy to use and affordable alternative to human viruses for routine water safety monitoring.